Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Jasa Penerbangan Batik Air Pada PT. Lion Group di Bandara Sultan Syarif Khasim II Pekanbaru - Jeli Nata Liyas (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2018)
This study aims to determine the effect of service quality on customer satisfaction atSultan Syarif Khasim II Airport Pekanbaru. Using a sample of 100 people. In this study theauthors use descriptive and quantitative research methods using SPSS method.From theresult of research, the value of titung variable of service quality is 20,764 and t value is table1,660, so t > t (20,764 > 1,660) and significant value 0,000 < 0,05, so it can be count tableconcluded that service quality variable positively and significant customer satisfaction. Thevalue of R square = 0,815 means 81,5% influence of independent variable (Service Quality)to dependent variable (Customer Satisfaction) equal to 81,5% and while remaining 18,5%influenced by other variable not examined.Finally from this study can be concluded thatcustomer satisfaction has a positive and significant impact on customer satisfaction, so it isadvisable to Air Batik airline to be able to maintain and continue to improve the quality ofservice.